ANALISIS PENGARUH KARIES GIGI TERHADAP KEJADIAN BARODONTOLGIA PADA KOMUNITAS PENYELAM DI KOTA MANADO - Mariati, Ni Wayan; Wahyuni, Rizka; Mintjelungan, Christy N; Galong, Junistika Priskila (JURNAL KEPERAWATAN, 2024)
Background: Indonesia has underwater beauty that attract tourists, both domestic and foreign tourists. Dental caries is the most prevalent oral disease. Barodontalgia is dental pain that occurs due to barometric pressure  changes in divers under certain conditions and is most commonly found in people with dental caries. Objective: This study aims to determine the effect of dental caries on the incidence of barodontalgia in the diving dcommunity in Manado. Methods: This type of research uses quantitative research with a cross-sectional research design. Sampling using purposive sampling of the diving community at the Dragonet diving center Malalayang, Manado City and the Youth Center Quay, Wenang District, Manado City from April to May 2024 with 31 divers as research subjects. Results: The results showed that DMF-T was included in the moderate criteria, with a total value of 125 and an average value of the entire population of 4.03. The results of Chi-Square statistical test showed a significance value (p = 0.695). Conclusion: The conclusion of this study is that the subjects' DMF-T is included in the moderate criteria and there is no significant relationship between the level of knowledge about barodontalgia and DMF-T. Keywords: Barontalgia; Caries; DMF-T; Drivers